Nursing and its role in obstetric emergencies of young mothers. - da Costa, Maria Vanessa; Sillva, Carla; Martins, João Claudio (Brazilian Journal of Implantology and Health Sciences, 2019)
The objective of the study is to describe the scientific evidence of nursing care in obstetric emergencies of adolescent mothers. This is an integrative literature review, carried out in the databases of the Virtual Health Library, Scientific and Technical Literature of Latin America and the Caribbean (LILACS), Online System Search and Analysis of Medical Literature (MEDLINE) and Base Nursing data (BDENF) as Descriptors Health Sciences (Decs)"Nursing performance." "Pregnant Women". Emergency and Rescue ServicesAssociated with the Boolean AND operator. The study included 23 original articles available in full, in Portuguese language between the years January 2014 to January 2019. And deleted, repeated 12 articles, monographs, dissertation and literature reviews. The final sample consisted of 11 articles divided into the following semantic categories: The actions of the nurse in the care of patients in the pre-eclampsia and the quality of nursing care in the perception of pregnant women with pre-eclampsia. It was observed that the urgent and emergency care to pregnant women with pre-eclampsia, nursing develops a direct assistance of great significance impact on the lives of these adolescents and their children.